2021
DOI: 10.26794/2308-944x-2021-9-2-6-28
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factors affecting FDI in developing Asian countries

Abstract: The paper focuses on various factors that affect the inflow of Foreign Direct Investment in developing countries. The study majorly deals with Asian countries, namely India, China, Myanmar, Nepal, Pakistan, Bangladesh and Bhutan, that are progressing from being aid-dependent to trading giants. The factors affecting FDI are majorly categorised into dependent and independent variables. Here, in this study, the dependent variable considered is FDI inflow, and independent variables are market size, the value of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The policymakers of Asian countries including India should take more initiatives to improvise the tools that might influence the growth and development of their economies [62]. Therefore, it is suggested that, if the country needs to increase its economic growth rate and productivity, it needs to work on redesigning the existing gender roles as well.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The policymakers of Asian countries including India should take more initiatives to improvise the tools that might influence the growth and development of their economies [62]. Therefore, it is suggested that, if the country needs to increase its economic growth rate and productivity, it needs to work on redesigning the existing gender roles as well.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%